REVIEW OF SATURATED STEAM PARAMETER IN DRUM LONGITUDINAL COIL BOILER BY USING SOLAR BUILDING - Tahdid, Tahdid (KINETIKA, 2017)
Steam power generation is power generation’s technology that using rankine cycle which the chemical energy from the fuel converted into heat to heating the water until became mechanical energy whose moved the turbin and then converted again into electricity in generator. Many factors affect the efficiency of steam power generation. Temperature and pressure are the main parameters of the measurement of their effectiveness. And the value of temperature and pressure is influenced by the volume level of the steam drum. It is therefore necessary to assess the volume level of the steam drum to obtain the appropriate steam drum volume level to obtain optimum steam power generation work. In this research, the variable of level volume used is 30%, 40%, 50%, and 60%. In condition of non-steady state saturated steam with operating conditions of AFR in 16,5 and fuel flow rate in 1,.51 l/h. The process is done until the target of 25 bar pressure is reached. And based on the research results obtained that the optimum conditions of boiler is at 50% level volume.